Values and Leadership: Theory Development, New Research, and an Agenda for the Future - Begley, Paul T. (Alberta Journal of Educational Research, 2000)
This article presents an updated account of values and valuation processes as they occur in school settings. A tradition of epistemological and philosophical debate, as well as the dominance of empiricist perspectives in educational administration, have tended to separate the consideration of values as influences on leadership practices from the usual organizational or social collective perspectives common to the field. More recently, however, powerful social forces such as globalization and the increasing diversity of our societies have stimulated increased academic productivity in this sector. A more balanced view of values as an influence on administration is emerging, which combines notions of the personal values manifested by individuals and the professional values of administration with the collective values manifested by groups, societies, and organizations. Discussion and inquiry have now extended beyond the usual expert opinion and academic debate of theorists and philosophers to include practitioners, empirical verifications of theory, and important new research findings. In this article key concepts from theory and a selection of findings from research are reviewed. The application of theory and research about values through reflective educational practice is discussed. Certain methodological problems associated with values research are examined, and the ground breaking work of several key contributors to the field is identified and considered. The article concludes with some speculations on an agenda for future theory-building and research in the values field.